Pau Kecik Enterprise / Fariesya Mohd Khaizal - Fariesya, Mohd Khaizal (2020)
This business plan report contains detail of a business named Pau Kecik Enterprise. It is a partnership business between the founder and her family. The product that being offered is pau which a traditional food origin from China. Founder get the idea to selling the pau is from her skill of making pau. The aim of this business is to get customers as much it can because the target market of this business are people from all ages and gender. Pau that is sell is soft so that youngsters and elders can eat them. In addition, since it is food industry, so either male or female can eat it. No specific requirement needed. Moreover, the competition among seller that sell pau is lower because not many of people sell it. That is one of the advantage that Pau Kecik Enterprise can get. Furthermore, profit of this busines will not be a problem because lot of people in the population loves to eat pau. So, even the founder take a little profit from the sales, she still get her own part of profitability. It is not a problem to worry about.